2013
DOI: 10.1055/s-0033-1351086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Newly Adapted Clip Marker System in Ultrasound-Guided Core Needle Biopsy for Suspicion of Breast Cancer

Abstract: Introduction !Women have a 10 % risk of developing breast cancer at some stage in their life. This makes breast cancer the most common type of cancer found in women and the most common cause of death for women between the ages of 35 and 55 years. In Germany, around 58 000 women develop breast cancer every year, and approximately 20 000 die of it [1]. The treatment options and the characteristics determining the choice of therapy in patients with primary advanced breast cancer are Abstract !

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…wire marking, which is particularly useful in patients with pathologic complete response after neoadjuvant chemotherapy [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…wire marking, which is particularly useful in patients with pathologic complete response after neoadjuvant chemotherapy [15].…”
Section: Discussionmentioning
confidence: 99%
“…This difficulty can be remedied using a marker clip to locate the primary breast tumor during sonographically guided core needle biopsy prior to surgical therapy or neoadjuvant chemotherapy [9 -12]. Based on the findings of our previous studies and using a marker clip system we had helped to develop and establish [13,14] we investigated the accuracy of an innovative clip marking method in patients with breast cancer [15]. Our previously published results confirmed that this innovation had pre-cisely adapted the stylet length of the marking system to the single-use breast biopsy system (HistoCore™).…”
Section: Introductionmentioning
confidence: 99%
“…Invasive breast cancer was confirmed histologically in all 25 patients by sonographically guided core needle biopsy using a single-use breast biopsy system (HistoCore™, BIP™ Biomedizinische Instrumente & Produkte GmbH, Germany) [13]. Intramammary clip marking was additionally done using a directly adapted clip system based on the established O-Twist Marker™ system (BIP™ Biomedizinische Instrumente & Produkte GmbH, Germany) [14,15]. All sonographically guided core needle biopsies and clip markings were performed by the same two experienced radiologists to exclude potential inter-observer variability.…”
Section: Sonographically Guided Core Needle Biopsy and Clip Markingmentioning
confidence: 99%
“…This difficulty can be remedied using a marker clip to locate the primary breast tumor during sonographically guided core needle biopsy prior to surgical therapy or neoadjuvant chemotherapy [9][10][11][12]. Based on the findings of our previous studies and using a marker clip system we had helped to develop and establish [13,14], we investigated the accuracy of an innovative clip marking method in patients with breast cancer [15]. Our previously published results confirmed that this innovation had precisely adapted the stylet length of the marking system to the singleuse breast biopsy system (HistoCore™).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation